American Neoconservatism: Rise and Fall of an Idea - Raffaella Baritono (Scienza & Politica, 2019)
After its rise, in the years of the George W. Bush Jr.’s  presidency, neoconservatism seemed to collapse under the weight of its utopian ambition to dictate the new rules of the internal and international political order, to stem the conflicts and processes of disruption of the liberal order as it had been defined since the Second World War. Going through the various contributions of the monographic issue, this introduction highlights the historical and political reasons that make neoconservatism an idea whose parable and movements are of great importance to understand the crisis of liberalism and the current role of the neoliberalism.